Investigating the antioxidant and antimicrobial activities of different vinegars - Bakir, Sena; Devecioglu, Dilara; Kayacan, Selma; Toydemir, Gamze; Karbancioglu-Guler, Funda; Capanoglu, Esra (SPRINGER, 2017)
In this study, the antioxidant contents and the antimicrobial activities of 18 vinegar samples were investigated. For this purpose, total flavonoid contents (TFC) and total phenolic contents (TPC) of different vinegar samples were determined. In addition, total antioxidant capacities (TAC) of vinegars were analyzed using four different in vitro tests: ABTS, CUPRAC, DPPH, and FRAP, in parallel. Results obtained from antioxidant analyses showed that balsamic vinegar had the highest TFC (96 +/- 18 mg CE/100 mL) and TPC values (255 +/- 24 mg GAE/100 mL), as well as the highest TAC determined using CUPRAC (709 +/- 108 mg Trolox/100 mL) and FRAP (421 +/- 28 mg Trolox/100 mL) methods. The phenolic profiles of vinegar samples were identified by performing HPLC analysis. Among all vinegar samples studied, the most abundant phenolic compounds were determined to be gallic acid, protocatechuic acid, and p-hydroxybenzoic acid. Furthermore, antimicrobial activities of different vinegars, against Staphylococcus aureus, Salmonella Typhimurium, and Escherichia coli, were evaluated using disc diffusion method; the results of which were related to the acetic acid contents and the pH values of the vinegar samples. Balsamic vinegar was again determined to be the sample that had the highest antimicrobial activity, which showed a strong antibacterial activity against S. Typhimurium. Antibacterial activities of vinegars could partly be related to both their acetic acid contents and the pH values, and also to their phenolic contents.
Keywords: Vinegar; Antioxidant capacity; Antimicrobial activity; Phenolic content; ESCHERICHIA-COLI O157-H7; LISTERIA-MONOCYTOGENES; ORGANIC-ACIDS; ACETIC-ACID; SALMONELLA-TYPHIMURIUM; BALSAMIC VINEGAR; PHENOLIC-ACIDS; GRAPE POMACE; RICE VINEGAR; CAPACITY; Food Science & Technology